Imaginários de violências e conflitos na relação professor/aluno - Oliveira, Eliane dos Santos Macedo (2017)
Societal relations free from pre-defined intentionalities, tribal cross-links, and the ambivalence that marks the wandering and the "being with" people, in the context of postmodernity, constitute the polysemy of everyday life, which is anodyne, banal and permeated by feelings of belonging and repulsion. The conflicts and violence, often resulted from feelings of revulsion among people, even though they are situated as negative processes, can be useful when divergent and disproportionate social relations occur between them, helping to prevent their suppression and annihilation. In this study, we aimed to apprehend the imaginary of conflicts and violence in the relationship between teachers and students. Firstly, because we understand that school is a sociocultural space where postmodern societal relations are mixed and confronting modern structures and organizations. Second, because we perceive that conflicts and violence in the relation between teachers and students are recurrent and if not understood in a contextual way, they can nullify the possibility of their perception as resistance to instituted powers and totalitarian violence. This qualitative research was composed by: the dialogue with authors (Gilbert Durand, Michel Maffesoli, Georg Simmel, Boaventura de Souza Santos, Carlos Gadea, among others) whose works are classic references in the discussions about imaginaries, postmodernity, violence and conflicts, addressed in the bibliographical research; by a document research contemplating the analysis of Minutes of the Pedagogical Team intending to clear the indicatives of totalitarian violence and suppressive referrals in pedagogical interventions; it was also constituted by field research, in which the framework was formed by semi-structured interviews with students and teachers, as well as by group interviews using the Focal Group technique with students from a state public education institution located in the metropolitan region of Campo Mourão, in the interior of Paraná State. The resulting data corpus from this research were organized based on the technique of Content Analysis and analyzed from the formist sociology, which allowed to reveal the confrontations between the imaginary of teachers and students, within the scope of their relations in the everyday school, in which has manifested itself from denials, confrontations, lack of dialogue between these characters, as well as a series of elements that denote the recurrence in which conflicts occur and express violence in the classroom context.